The Impact of Macroeconomic Announcements on Emerging Market Bonds - Andritzky, Jochen (IMF Working Papers; Working Paper ;, 2005)
This paper examines how emerging bond markets react to macroeconomic announcements. Global bond spreads respond to rating actions and changes in global interest rates rather than domestic data and policy announcements. All announcements affect market volatility. Data and policy announcements reduce uncertainty and stabilize the trading environment, while rating actions cause greater volatility. Results are broadly robust to country-specific and panel analyses, assuming conditional variance and controlling for the surprise content of news. In subsamples, announcements are found to matter less for countries with more transparent policies and higher credit ratings. In a crisis, rating actions become less important, and investors focus more on simple and timely indicators, like CPI.